A paf-based all-solid-state polymer electrolyte, a preparation method and applications
Patent Information
- Application Number
- CN202410201468.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-02-23
AI Technical Summary
目前固态或准固态电池中应用的高性能固体电解质主要包括:由玻璃和陶瓷制成的固体无机电解质、由聚合物基体和锂盐制成的不含液体溶剂的固体聚合物电解质(SPE),准固体聚合物电解质(QSPE),这些电解质能够有效克服与电极接触性能差的问题,此外这些电解质在应用过程中也存在一些问题,例如:QSPE中存在溶剂残留和机械性能较差,此外,由于Li+迁移效率和力学性能的限制,用于准固体复合电解质的聚合物基体,如聚偏二氟乙烯-六氟丙烯、聚丙烯腈和聚环氧乙烷将发生锂枝晶,最终对聚合物电解质的应用产生不利影响
[0021] Compared with existing technologies, the PAF-based all-solid-state polymer electrolyte obtained by the present invention through the synergistic control of raw materials, raw material ratios, processes, and process parameters has the following advantages:
Smart Images

Figure CN118472365B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer electrolytes, specifically relating to a PAF-based all-solid-state polymer electrolyte, its preparation method, and its application. Background Technology
[0002] With the emergence of various new energy devices such as smart wearable devices and electric vehicles, the development of high-energy-density and high-safety energy storage devices has become an urgent need. Lithium metal batteries, due to their large theoretical capacity (3860 mAh g / g), are a prime example. -1 The operating voltage (3.04V relative to the standard hydrogen electrode) is currently a highly attractive candidate. However, commercial liquid lithium batteries have some safety issues, such as short circuits and fires caused by leakage of low-boiling-point organic solvents in the electrolyte. Therefore, using solid-state or quasi-solid-state batteries to replace liquid batteries is an effective way to solve the safety problems of large energy storage devices such as electric vehicles. Currently, the high-performance solid electrolytes used in solid-state or quasi-solid-state batteries mainly include: solid inorganic electrolytes made of glass and ceramics, solid polymer electrolytes (SPE) made of polymer matrix and lithium salt without liquid solvents, and quasi-solid polymer electrolytes (QSPE). These electrolytes can effectively overcome the problem of poor electrode contact performance. In addition, these electrolytes also have some problems in application, such as solvent residue and poor mechanical properties in QSPE. Furthermore, due to the presence of low-boiling-point organic solvents in the electrolyte, the high operating voltage (3.04V relative to the standard hydrogen electrode) is a significant factor. + Limitations in migration efficiency and mechanical properties lead to lithium dendrite formation in polymer matrices used in quasi-solid composite electrolytes, such as polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, and polyethylene oxide, ultimately negatively impacting the application of polymer electrolytes. Furthermore, polymer electrolytes exhibit low ionic conductivity at low temperatures, failing to meet the normal operation requirements of lithium-ion batteries under such conditions. Therefore, obtaining polymer electrolytes with high safety, high stability, high mechanical properties, high conductivity, and high proton conductivity even at low temperatures remains a pressing technical challenge. Summary of the Invention
[0003] To address the aforementioned technical challenges, this invention provides a PAF-based all-solid-state polymer electrolyte, the preparation method of which includes the following steps:
[0004] Step 1: Mix lithium-rich PAF material and functional polymer in a solvent and stir at 15-40°C for 24-48 hours to obtain spinning solution;
[0005] The solvent is one or any combination of N-pyrrolidone, N,N-dimethylformamide, acetone or triethylamine; the functional polymer is one or any combination of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) or polyvinyl alcohol (PVA), the mass ratio of the functional polymer to the lithium-rich PAF material is 1 to 25:1, and the mass ratio of the mixture of the functional polymer and the lithium-rich PAF material to the solvent is 1:1 to 10;
[0006] Step 2: Mix lithium salt and polyethylene oxide (PEO) in a solvent and stir at 15-40°C for 24-48 hours to obtain a spraying solution;
[0007] The solvent is one or any combination of acetonitrile, N,N-dimethylformamide or triethylamine; the lithium salt is one or any combination of LiTFSI, LiClO4 or LiFSI, and the mass ratio of lithium salt to PEO is 1:1 to 5.
[0008] Step 3: Under room temperature conditions, electrospinning / solution spraying is performed on the spinning solution obtained in Step 1 and the spraying solution obtained in Step 2 to obtain PAF-based all-solid polymer electrolyte. The electrospinning is performed with a voltage of 12-19KV, a pushing speed of 0.5-5mL / h, and a scanning speed of 5-20mm / s.
[0009] Furthermore, the preparation method of the lithium-rich PAF material includes the following steps:
[0010] Step 1:
[0011] Under nitrogen protection, monomer one and monomer two were added to the solvent at a molar ratio of 1:1 to 3, followed by the addition of tetra(triphenylphosphine)palladium and cuprous iodide. After 1 to 4 cycles, each cycle consisted of: cooling with liquid nitrogen at -196°C, evacuation, nitrogen purging, holding at 40 to 60°C, and then reacting at 80 to 120°C for 40 to 55 hours. After washing, the material was vacuum dried at 60 to 80°C for 12 to 48 hours to obtain the polyhydroxy PAF material.
[0012] The monomer one is one or any combination of 1,3,5-tris(4-ethynylphenyl)benzene, 1,3,5-triethynylbenzene, or 1,4-diethylbenzene; the monomer two is one or any combination of 2,5-dibromohydroquinone, 2,5-dibromophenol, or 2,4,6-tribromoresorcinol; the solvent is one or any combination of methanol, N,N-dimethylformamide, acetonitrile, acetone, triethylamine, or N-pyrrolidone; and the molar ratio of monomer one: monomer two: tetra(triphenylphosphine)palladium: cuprous iodide is 1-5: 1.5-10: 0.1-3: 0.1-3.
[0013] Step 2:
[0014] Under nitrogen protection, the polyhydroxy PAF material obtained in step 1 was mixed with lithium hydride in a solvent and reacted at 60–80 °C for 2–5 h. Then, lithium 3-chloropropanesulfonyl (trifluoromethanesulfonyl)imide (LiCPSI) was added and reacted at 80–100 °C for 24–48 h. After washing, the mixture was vacuum dried at 60–80 °C for 12–48 h to obtain lithium-rich PAF material.
[0015] The solvent is one or any combination of N,N-dimethylformamide, acetonitrile, acetone or N-pyrrolidone;
[0016] The mass ratio of the polyhydroxy PAF material to lithium hydride is 1:5 to 20;
[0017] The mass ratio of the polyhydroxy PAF material to LiCPSI is 1:0.5-5;
[0018] The lithium-rich PAF material described herein is a polyhydroxy porous aromatic framework material.
[0019] This invention also provides the application of PAF-based all-solid-state polymer electrolytes in lithium-ion batteries.
[0020] The beneficial effects of this invention are:
[0021] Compared with existing technologies, the PAF-based all-solid-state polymer electrolyte obtained by the present invention through the synergistic control of raw materials, raw material ratios, processes, and process parameters has the following advantages:
[0022] This invention provides an all-solid-state polymer electrolyte for high capacity and low-temperature resistance. Through synergistic control of raw materials, formulation, preparation method, and related parameters, effective interactions between various functional groups are achieved. A mixture of PEO and lithium salt is uniformly sprayed and filled into an electrospun nanofiber network, forming a dense membrane material with a stable electrolyte / lithium anode interface. This effectively suppresses lithium dendrite formation and prevents short circuits, resulting in excellent electrochemical stability of the battery. Furthermore, in the lithium-rich PAF material with high specific surface area and high lithium content, anions are confined to the three-dimensional framework of the PAFs, since only Li... + The free movement of these ions increases the lithium-ion transport number and significantly reduces concentration polarization. Simultaneously, the abundant three-dimensional transport channels in the polymer electrolyte enable Li... + Uniform and orderly dispersion and rapid transport. Results show that, compared with existing technologies, the electrolyte obtained in this invention exhibits superior electrochemical performance; at room temperature, the ionic conductivity of the electrolyte obtained in this invention is ≥3.31 × 10⁻⁶. -4 S cm -1 The lithium-ion transference number is ≥0.77, and the electrochemical window is ≥4.65V (vs Li).+ / Li); and it still exhibits good electrochemical performance at low temperatures, for example, at -20℃, the polymer electrolyte ionic conductivity is ≥5.32×10 -5 S cm -1 The all-solid-state polymer electrolyte of this invention has high yield, simple operation, and widely available raw materials, showing good application prospects in the field of lithium-ion batteries and is suitable for industrial production. Attached Figure Description
[0023] Figure 1 The image shows a comparison of the infrared spectra of PAF-228, LiCPSI, and PAF-228-Li obtained in Example 1 of this invention.
[0024] Figure 2 This is a cycle performance curve of a battery assembled with the all-solid-state polymer electrolyte PAF-228-Li / PVDF / PEO obtained in Example 1 of the present invention.
[0025] Figure 3 The diagram shows the AC impedance of PAF-228-Li / PVDF / PEO obtained in Example 1 of this invention. The inset shows the AC impedance before and after polarization.
[0026] Figure 4 The AC impedance spectrum of the all-solid polymer electrolyte PAF-228-Li / PVDF / PEO obtained in Example 1 of this invention is fitted with the Arrhenius equation.
[0027] Figure 5 This is an electrochemical window test curve of the all-solid polymer electrolyte PAF-228-Li / PVDF / PEO obtained in Example 1 of the present invention after being assembled into a battery;
[0028] Figure 6 The impedance EIS diagram is shown for the assembly of the polymer electrolyte PAF-228-Li / PVDF / PEO (containing plasticizer) obtained in Example 1 of this invention into SS / / PAF-228-Li / PVDF / PEO / / SS. Detailed Implementation
[0029] Example
[0030] The present invention is further illustrated below with specific embodiments. These embodiments are only for illustrating the present invention and are not intended to limit the scope of the present invention.
[0031] Example 1
[0032] (1) Under nitrogen purging, 1,3,5-tris(4-ethynylphenyl)benzene (189 mg) and 2,5-dibromohydroquinone (200.9 mg) were added to a mixed solution of N,N-dimethylformamide (DMF) and triethylamine (DMF to triethylamine volume ratio 1:1), and tetra(triphenylphosphine)palladium (75 mg) and cuprous iodide (25 mg) were added; the mixture was then cooled with liquid nitrogen at -196 °C, evacuated, purged with nitrogen, and heated at -50 °C. This process was repeated three times. After reacting at 105 °C for 48 h, the mixture was washed with a DMF / acetonitrile mixed solution and methanol at a volume ratio of 1:1, and then dried under vacuum at 60 °C for 12 h to obtain PAF-228.
[0033] (2) Under nitrogen protection, 200 mg of PAF-228 obtained in step (1) was mixed with 1 g of lithium hydride in 20 mL of DMF and reacted at 60 °C for 3 h. Then, 278 mg of LiCPSI was added and reacted at 90 °C for 48 h. After washing with a mixture of ethanol and water, the mixture was vacuum dried at 60 °C for 12 h to obtain PAF-228-Li material, the structure of which is as follows:
[0034]
[0035] (3) Under vacuum conditions, 100 mg of PAF-228-Li material obtained in step (2) and 900 mg of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) were mixed in 4 g of ultra-dry N,N-dimethylformamide to obtain a spinning solution. At the same time, 0.287 g of LiTFSI and 0.528 g of PEO were dissolved in 11.6 g of acetonitrile to prepare a spraying solution. The solution was stirred at room temperature for 12 h. Electrospinning was carried out under the conditions of a voltage of 14.52 KV, a spinning solution push rate of 1 mL / h and a spraying solution push rate of 10 mL / h to obtain an all-solid polymer electrolyte PAF-228-Li / PVDF / PEO.
[0036] Electrochemical tests were conducted on a battery assembled from PAF-228-Li / PVDF / PEO at room temperature. The ionic conductivity at room temperature was 5.48 × 10⁻⁶. -4 S cm -1 The activation energy is 0.0953 eV, and the initial discharge specific capacity at 0.2C is 166 mAh g. -1 After 400 cycles, the coulombic efficiency was 99%, the lithium-ion transference number was 0.81, and the electrochemical window was 4.85 V. With the addition of a plasticizer (EDFA / FEC, v:v = 9:1), the ionic conductivity at -20 °C was 3.43 × 10⁻⁶. -4 S cm -1 .
[0037] Example 2
[0038] (1) Under nitrogen purging, 1,3,5-triethynylbenzene (150.2 mg) and 2,5-dibromohydroquinone (267.9 mg) were added to a mixed solution of N,N-dimethylformamide (DMF) and triethylamine (DMF to triethylamine volume ratio of 1:1), and tetra(triphenylphosphine)palladium (70 mg) and cuprous iodide (20 mg) were added; the mixture was then cooled with liquid nitrogen at -196 °C, evacuated, purged with nitrogen, and heated at -50 °C. This process was repeated three times. After reacting at 100 °C for 36 h, the mixture was washed with a DMF / acetonitrile mixed solution and methanol at a volume ratio of 1:1, and then dried under vacuum at 70 °C for 20 h to obtain PAF-228-2.
[0039] (2) Under nitrogen protection, 200 mg of PAF-228-2 material obtained in step (1) was mixed with 1200 mg of lithium hydride in 22 mL of DMF and reacted at 60 °C for 3 h. Then, 301 mg of LiCPSI was added and reacted at 90 °C for 48 h. After washing with a mixture of ethanol and water, the mixture was vacuum dried at 70 °C for 12 h to obtain PAF-228-2-Li material, the structure of which is as follows:
[0040]
[0041] (3) Under vacuum conditions, 80 mg of PAF-228-2-Li material obtained in step (2) and 920 mg of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) were mixed in 4 g of ultra-dry N,N-dimethylformamide to obtain a spinning solution. At the same time, 0.287 g of LiTFSI and 0.44 g of PEO were dissolved in 12.5 g of acetonitrile to prepare a spraying solution. The solution was stirred at room temperature for 12 h. Electrospinning was carried out under the conditions of a voltage of 16.02 KV, a spinning solution push rate of 1.5 mL / h and a spraying solution push rate of 10 mL / h to obtain an all-solid polymer electrolyte PAF-228-Li2 / PVDF / PEO.
[0042] (4) The PAF-228-2-Li / PVDF / PEO battery was assembled at room temperature and electrochemical tests were performed. Its ionic conductivity at room temperature was 3.55 × 10⁻⁶. -4 S cm -1 The activation energy is 0.103 eV, and the initial discharge specific capacity at 0.2C is 156 mAh g. -1 After 400 cycles, the coulombic efficiency was 99%, the lithium-ion transference number was 0.83, and the electrochemical window was 4.65 V. With the addition of a plasticizer (EDFA / FEC, v:v = 4:1), the ionic conductivity at -20 °C was 2.01 × 10⁻⁶. -4 S cm -1 .
[0043] Example 3
[0044] (1) Under nitrogen purging, 1,3,5-tris(4-ethynylphenyl)benzene (189 mg) and 2,5-dibromophenol (189 mg) were added to a mixed solution of N,N-dimethylformamide (DMF) and triethylamine (DMF to triethylamine volume ratio of 1.2:1), and tetra(triphenylphosphine)palladium (85 mg) and cuprous iodide (35 mg) were added; the product was then cooled with liquid nitrogen at -196 °C, evacuated, purged with nitrogen, and heated at 60 °C. This process was repeated three times. After reacting at 105 °C for 48 h, the product was repeatedly washed with a DMF / acetonitrile mixed solution and methanol at a volume ratio of 2:1. After vacuum drying at 65 °C for 20 h, PAF-228-3 was obtained.
[0045] (2) Under nitrogen protection, 200 mg of PAF-228-3 material obtained in step (1) was mixed with 1400 mg of lithium hydride in 20 mL of DMF and reacted at 70 °C for 4 h. Then, 208 mg of LiCPSI was added and reacted at 100 °C for 36 h. After washing with ethanol and water, the mixture was vacuum dried at 70 °C for 36 h to obtain PAF-228-3-Li material, the structure of which is as follows:
[0046]
[0047] (3) Under vacuum conditions, 120 mg of PAF-228-3-Li material obtained in step (2) and 880 mg of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) were mixed in 4 g of ultra-dry N,N-dimethylformamide to obtain a spinning solution. At the same time, 0.287 g of LiTFSI and 0.616 g of PEO were dissolved in 14.4 g of acetonitrile to prepare a spraying solution. The solution was stirred at room temperature for 12 h. Electrospinning was carried out under the conditions of a voltage of 14.02 KV, a spinning solution push rate of 1 mL / h and a spraying solution push rate of 10 mL / h to obtain an all-solid polymer electrolyte PAF-228-Li3 / PVDF / PEO.
[0048] (4) The PAF-228-3-Li / PVDF / PEO battery was assembled at room temperature and electrochemical tests were performed. Its ionic conductivity at room temperature was 3.31 × 10⁻⁶. -4 S cm -1 The activation energy is 0.0993 eV, and the initial discharge specific capacity at 0.2C is 164 mAh g. -1 After 400 cycles, the coulombic efficiency was 99%, the lithium-ion transference number was 0.77, and the electrochemical window was 4.67 V. With the addition of a plasticizer (EDFA / FEC, v:v = 1:1), the ionic conductivity at -20 °C was 5.32 × 10⁻⁶. -5 S cm -1 .
[0049] Comparative Example 1
[0050] Article Title: PVDF-HFP / LiTFSI Composite Solid Electrolyte, Li 6.25 Ga 0.25 La3Zr2O 12 Doped PVDF-H FP / LiTFSI based composite solid state electrolyte with different micromorphology of Li 6.25 Ga 0.25 La3Zr2O 12 doping.
[0051] Journal: Journal of Alloys and Compounds, 968(2023)171872
[0052] Authors: Jingxuan Cai, Tao Liu, Chuwei Liu, Guoqiang Liu
[0053] Methods: Solid electrolytes are a safer alternative to liquid electrolytes. Adding Ga to lithium lanthanum zirconium oxide (LLZO) garnet-based solid electrolytes can effectively improve their performance. Solid electrolytes prepared by electrospinning and sol-gel methods have different properties, directly affecting the electrochemical performance of the assembled battery. This study prepared Li... 6.25 Ga 0.25 La3Zr2O 12 (Ga-LLZO) nanoparticles and nanofibers. The battery is also assembled from a composite film consisting of a poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP) polymer substrate within a Ga-LLZO ceramic filler. The electrolyte prepared using Ga-LLZO nanofibers exhibits good conductivity. A Li|10wt%Ga-LLZO nanofibers / PVDF-HFP / 60wt% lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)|LiFePO4 battery was prepared in a comparative manner. At 0.2C, the initial discharge specific capacity of this battery was 119.5 mAh g. -1 Its electrochemical window reaches 4.4V (Li / Li) at room temperature. + Its room temperature ionic conductivity is 1.1 × 10⁻⁶. -4 S cm -1 .
[0054] Comparative Example 2
[0055] Title: Semi-interpenetrating-network PEO-based polymer electrolytes with fast Li-ion conduction for solid Li-metal batteries.
[0056] Journal: Journal of Energy Storage, 73(2023)108809 Authors: Ying Jiang, Nan Guo, Feilong Dong, Haiming Xie, Jun Liu
[0057] Methods: A semi-interpenetrating network (Semi-IPN) polyethylene oxide (PEO)-based solid polymer electrolyte (SPE) for lithium metal batteries was synthesized. The solid polymer electrolyte exhibited great flexibility, with an ionic conductivity of 2.45 × 10⁻⁶ at room temperature. -4 S cm -1 When assembled into a LiFePO4|SiN|Li battery, its initial discharge specific capacity at room temperature and 0.2C is 150 mAh g. -1 .
[0058] manual Figure 1 Infrared testing
[0059] like Figure 1 As shown, a 1179 cm⁻¹ can be observed in PAF-228-Li. -1 The presence of a distinct absorption peak at the point indicates that LiCPSI was successfully grafted onto the PAF-228-Li material, which is the tensile vibration peak of -SN- in LiCPSI.
[0060] manual Figure 2 Cyclic performance test
[0061] A Li / / PAF-228-Li / PVDF / PEO / / LFPCR2025 coin cell was assembled using LiFePO4 as the positive electrode and lithium foil as the negative electrode, and its cycle performance was tested. Figure 2 As shown, at 0.2C, the initial discharge specific capacity of the PAF-228-Li / PVDF / PEO battery prepared in Example 1 was 166 mAh g. -1 After 400 cycles, the coulombic efficiency remained stable at 99% or above, indicating that PAF-228-Li / PVDF / PEO has good electrochemical stability.
[0062] manual Figure 3 Lithium-ion transference number test
[0063] The PAF-228-Li / PVDF / PEO prepared in Example 1 was tested using the chronoamperometry method, and the lithium-ion transference number (t) in the electrolyte was calculated using the Bruce Vincent equation. Li + The value was 0.81, far higher than that of traditional dual-ion batteries, indicating that the anions in the system were fixed on the carbon framework, with only Li... + It can move freely, which significantly improves t Li + This reduces concentration polarization.
[0064] manual Figure 4 Arrhenius equation diagram;
[0065] By performing Arrhenius fitting on ionic conductivity and temperature, such as Figure 4 As shown, the fitting results conform to the Arrhenius curve, indicating that the conduction of lithium ions in PAF-228-Li / PVDF / PEO follows a hopping mechanism. The calculated activation energy of PAF-228-Li / PVDF / PEO is 0.0953 eV, which is lower than the activation energies reported for most electrolytes.
[0066] manual Figure 5 Electrochemical window test curve.
[0067] like Figure 5 As shown, Li / / PAF-228-Li / PVDF / PEO / / SS was tested using linear sweep voltammetry (LSV) in the voltage range of 3.0–5.5 V and at a scan rate of 1 mV / s. -1 This indicates that the electrolyte oxidation stability voltage is 4.85V, which has a wide electrochemical window and good electrochemical stability.
[0068] manual Figure 6 Low-temperature ionic conductivity.
[0069] The ionic conductivity of the electrolyte (containing plasticizer) at -20℃ was calculated based on the electrochemical impedance spectroscopy method. Figure 6 As shown, the bulk impedance of this electrolyte is 5.94Ω. Figure 6 The calculated electrolyte ionic conductivity is 3.43 × 10⁻⁶. -4 S cm -1 This indicates that it still has high ionic conductivity at low temperatures.
[0070] In summary, compared with existing technologies, the materials obtained in the embodiments of this invention all exhibit superior electrochemical performance. Furthermore, while the raw materials, proportions, and process parameters used in each embodiment differ, the electrochemical stability of the obtained polymer electrolytes varies. Additionally, the electrolytes obtained in this invention maintain good performance at low temperatures; at -20°C, the ionic conductivity is ≥5.32 × 10⁻⁶. -5 S cm -1 The polymer electrolyte material with excellent performance at both room temperature and low temperature obtained by this invention has not been reported in the prior art. Therefore, the performance of the polymer electrolyte obtained by this invention is determined by the synergistic effect of raw materials, reaction ratios, and process conditions and parameters.
Claims
1. A PAF-based all-solid-state polymer electrolyte, characterized in that, Its preparation method includes the following steps: Step 1: Mix lithium-rich PAF material and functional polymer in a solvent and stir at 15~40℃ for 24~48 h to obtain spinning solution; The solvent is one or any combination of N-pyrrolidone, N,N-dimethylformamide, acetone or triethylamine; the functional polymer is one or any combination of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene or polyvinyl alcohol, the mass ratio of the functional polymer to the lithium-rich PAF material is 1 to 25:1, and the mass ratio of the mixture of the functional polymer and the lithium-rich PAF material to the solvent is 1:1 to 10. Step 2: Mix lithium salt and polyethylene oxide in a solvent and stir at 15~40℃ for 24~48 h to obtain a spraying solution; The solvent is one or any combination of acetonitrile, N,N-dimethylformamide or triethylamine; the lithium salt is one or any combination of LiTFSI, LiClO4 or LiFSI, and the mass ratio of lithium salt to PEO is 1:1~5. Step 3: Under room temperature conditions, the spinning solution obtained in Step 1 and the spraying solution obtained in Step 2 are subjected to electrospinning / solution spraying to obtain PAF-based all-solid polymer electrolyte. The electrospinning is performed with a voltage of 12~19 KV, a pushing speed of 0.5~5 mL / h, and a scanning speed of 5~20 mm / s. The preparation method of the lithium-rich PAF material described in step 1 includes the following steps: (1) Under nitrogen protection, monomer one and monomer two were added to the solvent at a molar ratio of 1:1 to 3, followed by tetra(triphenylphosphine)palladium and cuprous iodide. After 1 to 4 cycles, each cycle was as follows: cooling with liquid nitrogen at -196℃, evacuating, purging with nitrogen, holding at 40 to 60℃, and reacting at 80 to 120℃ for 40 to 55 h. After washing, the material was vacuum dried at 60 to 80℃ for 12 to 48 h to obtain the polyhydroxy PAF material. The monomer one is one or any combination of 1,3,5-tris(4-ethynylphenyl)benzene, 1,3,5-triethynylbenzene, or 1,4-diethylbenzene; the monomer two is one or any combination of 2,5-dibromohydroquinone, 2,5-dibromophenol, or 2,4,6-tribromoresorcinol; the solvent is one or any combination of methanol, N,N-dimethylformamide, acetonitrile, acetone, triethylamine, or N-pyrrolidone; and the molar ratio of monomer one: monomer two: tetra(triphenylphosphine)palladium: cuprous iodide is 1-5: 1.5-10: 0.1-3: 0.1-3. (2) Under nitrogen protection, the polyhydroxy PAF material obtained in step (1) is mixed with lithium hydride in a solvent and reacted at 60~80℃ for 2~5 h. Then, 3-chloropropanesulfonyl (trifluoromethanesulfonyl)imide lithium is added and reacted at 80~100℃ for 24~48 h. After washing, it is vacuum dried at 60~80℃ for 12~48 h to obtain lithium-rich PAF material. The solvent is one or any combination of N,N-dimethylformamide, acetonitrile, acetone or N-pyrrolidone; The mass ratio of the polyhydroxyl PAF material to lithium hydride is 1:5~20; The mass ratio of the polyhydroxy PAF material to LiCPSI is 1:0.5~5; The lithium-rich PAF material described herein is a polyhydroxy porous aromatic framework material.
2. The application of the PAF-based all-solid-state polymer electrolyte as described in claim 1 in lithium-ion batteries.
Citation Information
Patent Citations
Single-ion quasi-solid polymer electrolyte, preparation method and application thereof
CN116014237A
Lithium-rich PAF composite single-ion quasi-solid polymer electrolyte, preparation method and application
CN116706225A
Solid electrolyte, and preparation method therefor and application thereof
US20200403266A1